Development of Ferrero Nutrition Criteria: category-specific, progressive guidelines for product innovation - Canzoneri, Federico; Charron, Mélanie; Drewnowski, Adam; Alzari, Emanuela; Biolatti, Marta; Cavalli, Emanuela; Franci, Marco; Giri, Stefania; Maingrette, Fritz; Maj, Maria Malgorzata; Manera, Ileana; Rosso, Ginevra; et al. (Frontiers in Nutrition, 2025)
BackgroundNutrition standards developed for internal use can help assess nutrient density and guide improvements in company product portfolios. Often category-specific, such standards are used to guide product innovation and new product development.ObjectiveTo develop Ferrero Nutrition Criteria (FNC), a new set of progressive nutrition standards for internal use to evaluate product portfolio and to guide product formulation and development.MethodsThe FNC was developed with reference to a publicly available database, the Food and Nutrient Database for Dietary Studies (FNDDS 2017-18) and the corresponding Food Pattern Equivalents Database (FPED), both maintained by the US Department of Agriculture. Nutrition standards were based on recommendations issued by international agencies and other expert bodies, pledges that regulate advertising and marketing to children, other existing nutrient profiling models, consumer trends, technological constraints, the nutritional composition of Ferrero products and their taste performance. Minimum values for nutrients and ingredients to encourage were based on dietary guidelines.ResultsThe FNC model was used to assign foods and beverages into three classes that were largely based on energy and on nutrients to limit (added sugar, saturated fat and sodium). Among nutrients to encourage were protein, fiber, vitamins, minerals and among ingredients to encourage were dairy, nuts, fruits, whole grains, legumes, seeds and vegetables. The setting of category specific criteria also took into account taste, portion size, eating occasions, and role of the food or beverage in the overall diet. The FNC model is intended to be progressive and to evolve continually as new products are developed.ConclusionThe FNC model reflects Ferrero’s commitment to transparency and the promotion of responsible consumption. It will be used to guide improvements in the Ferrero product portfolio.